2018
DOI: 10.1101/318402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systems biology approach uncovers the core gene regulatory network governing iridophore fate choice from the neural crest

Abstract: Multipotent neural crest (NC) progenitors generate an astonishing array of derivatives, including neuronal, skeletal components and pigment cells (chromatophores), but the molecular mechanisms allowing balanced selection of each fate remain unknown. In zebrafish, melanocytes, iridophores and xanthophores, the three chromatophore lineages, are thought to share progenitors and so lend themselves to investigating the complex gene regulatory networks (GRNs) underlying fate segregation of NC progenitors. Although t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(40 citation statements)
references
References 46 publications
7
32
1
Order By: Relevance
“…In a recent detailed study, we demonstrated that, indeed, tfec serves as a robust marker of the iridophore lineage, allowing us to define the major stages of iridophore development [14].…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…In a recent detailed study, we demonstrated that, indeed, tfec serves as a robust marker of the iridophore lineage, allowing us to define the major stages of iridophore development [14].…”
Section: Introductionmentioning
confidence: 86%
“…Characterisation of the phenotypes of mutants affecting multiple NC derivatives has been widely used to infer the identities and potencies of these progenitors. In the pigment cell field, a progressive fate restriction model has been developed, with both a multipotent chromatoblast and a bipotent melano-iridoblast as identified partially-restricted intermediates ( [10] [11]- [14]). Studies of fate-specification mutants further permits elucidation of the gene regulatory networks (GRNs) governing diversification of these precursors ( [14], [15]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations